Reduced expression of sushi domain containing 2 is associated with progression of non-small cell lung cancer - CAI, CUIXIA (Oncol Lett, 2015)
Sushi domain containing 2 (SUSD2) has been identified as a gene encoding an 822-amino acid protein, which contains a transmembrane domain and functional domains inherent to adhesion molecules. Previous studies have reported that increased expression of SUSD2 has a critical role in tumorigenesis in human breast cancer. However, to the best of our knowledge, SUSD2 expression status and its correlation with the clinicopathological features of non-small cell lung cancer (NSCLC) have not previously been investigated. In the present study, reverse transcription-quantitative polymerase chain reaction and western blotting were used to evaluate SUSD2 messenger RNA (mRNA) and protein expression in NSCLC and adjacent normal lung tissues. The clinicopathological significance of SUSD2 was investigated by immunohistochemical analysis of an NSCLC tissue microarray. Receiver operating characteristic analysis was used to determine the cut-off score for positive expression of SUSD2. Furthermore, the correlation between SUSD2 expression and the clinicopathological features of NSCLC was analyzed by χ(2) test. The results revealed that SUSD2 mRNA (P<0.0001) and protein (P<0.0001) expression levels were significantly decreased in NSCLC tissues compared with those of adjacent normal tissues. When the SUSD2 positive expression percentage was determined to be >47.5% (area under ROC curve, 0.799; P<0.000), positive expression of SUSD2 was observed in 100% (32/32) of normal lung tissues and 55% (88/160) of NSCLC tissues by immunohistochemistry (χ(2)=21.160; P<0.000). Furthermore, it was demonstrated that the reduced SUSD2 protein levels in cancer tissues were positively correlated with poor histological grade (χ(2)=41.764; P<0.000), advanced clinical stage (χ(2)=10.790; P=0.013), higher pT (χ(2)=9.070; P=0.028) and positive regional lymph node metastasis (χ(2)=15.399; P=0.002). In conclusion, these data suggest that the reduced expression of SUSD2 is associated with the progression of NSCLC and may have a role in the pathogenesis of NSCLC.